A brown wave of riparian woodland mortality following groundwater declines during the 2012–2019 California drought. (28th July 2021) - Kibler, Christopher L; Schmidt, E Claire; Roberts, Dar A; Stella, John C; Kui, Li; Lambert, Adam M; Singer, Michael Bliss
Abstract: As droughts become more frequent and more severe under anthropogenic climate change, water stress due to diminished subsurface supplies may threaten the health and function of semi-arid riparian woodlands, which are assumed to be largely groundwater dependent. To better support the management of riparian woodlands under changing climatic conditions, it is essential to understand the sensitivity of riparian woodlands to depth to groundwater (DTG) across space and time. In this study, we examined six stands of riparian woodland along 28 km of the Santa Clara River in southern California. Combining remote sensing data of fractional land cover, based on spectral mixture analysis, with historical groundwater data, we assessed changes in riparian woodland health in response to DTG during the unprecedented 2012–2019 California drought. We observed a coherent 'brown wave' of tree mortality, characterized by decreases in healthy vegetation cover and increases in dead/woody vegetation cover, which progressed downstream through the Santa Clara River corridor between 2012 and 2016. We also found consistent, significant relationships between DTG and healthy vegetation cover, and separately between DTG and dead/woody vegetation cover, indicating that woodland health deteriorated in a predictable fashion as the water table declined at different sites and different times. Based on these findings, we conclude that the brown wave of vegetation dieback was likely caused by local changes in DTG associated with the propagation of precipitation deficits into a depleted shallow alluvial aquifer. These factors suggest that semi-arid riparian woodlands are strongly dependent on shallow groundwater availability, which is in turn sensitive to climate forcing.